Impact of Political Songs in Shaping Political Narratives in Pakistan - Sheikh, Rameesha; Dr. Zafar Iqbal (Journal of Peace, Development and Communication, 2024)
The technological advancements urged political parties to adopt modern rhetorical tactics to engage the youth, forming a sizeable chunk of Pakistan’s population. This study evaluates the influence of political songs on shaping political narratives, particularly in the context of audience behavioral patterns and gender dynamics. The research laid its foundation in framing theory and the KAB Model. The political songs of three major political parties, PPP, PMLN, and PTI, were selected. The study adopted a quantitative approach by conducting surveys among 330 respondents, including pilot testing, aged 18-65, based in Islamabad and Rawalpindi. Considering the nature of the study, a heterogeneous methodology encompassing multi-stage sampling, including stratified and convenient sampling techniques, is adopted. The results highlighted that PTI’s song gauged females' attention more than others and influenced the behavioral patterns of listeners. The revolutionary-themed song stands out for major political parties than other themes. This research contributes to a deeper understanding of mechanisms through which political narratives are shaped and disseminated.